Women's health : across age and frontier - World Health Organization (Geneva : WHO, 1992)
A visual presentation of selected facts and figures that document the infrior health status of women and illustrate the many gender-specific factors that contribute to health problems and undermine the ability of women to improve their lives. Facts and figures are used to demonstrate the complex determinants of female health status in different countries and at different stages throughout the lifespan, moving from discrimination against the female fetus to the health problems of elderly women. The book has eight chapters. The first illustrates the inferior status of women as demonstrated by sex-specific differences in education, income, participation in the labour force, wages earned, and other socioeconomic determinants. The second chapter, concerned with infancy and childhood, reveals early discrimination against females as seen through gender differences in aborted fetuses, feeding practices, nutritional status, incidence rates of selected diseases, and death rates among 2-5-year-olds. A chapter devoted to health status during adolescence presents data on the reproductive health, including rates of sexually transmitted diseases, of adolescent girls and on differences in alcohol and drug use in young men and women. Other chapters consider health risks linked to the type and amount of work done by women, the determinants of morbidity and mortality during pregnancy and childbirth, and the complex problems that underlie sex-specific differences in major diseases and infections. The concluding chapters document the seriousness of violence against women and the prevalence of mental disorders, and discuss the emerging health problems of elderly women.
Keywords: Women's Health -- statistics; Maternal and Child Health -- statistics